2020
DOI: 10.24251/hicss.2020.473
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cyber Security Awareness within Groups of Medical Professionals in Poland

Abstract: The goal of this study is to measure the cyber security awareness of medical professionals in Poland, i.e. to verify whether healthcare specialists have knowledge and understanding of basic cyber security threats. This survey was based on the cyber security recommendations from the European Union Agency for Network and Information Security and the U.S. Department of Health and Human Services. The survey consisted of 23 single and multiple-choice questions divided into four parts. The results categorized the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Regarding the non-ICT personnel, comparing our findings ( Table 1 ) with a 2020 study in Poland [ 21 ], a 2019 study in a health region of western Finland [ 22 ], and a 2019 study in a health organization in western Canada [ 19 ], revealed the low level of cybersecurity awareness status. In Institutions A, B, and C, the 22.7% that felt sufficiently trained in security and the 23.3% that perceived the importance of the terminals’ content to hackers, appeared significantly lower next to the 51.31% of the 1200 Finnish professionals reporting bring sufficiently aware of the information and the cybersecurity matters pertaining to their job.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Regarding the non-ICT personnel, comparing our findings ( Table 1 ) with a 2020 study in Poland [ 21 ], a 2019 study in a health region of western Finland [ 22 ], and a 2019 study in a health organization in western Canada [ 19 ], revealed the low level of cybersecurity awareness status. In Institutions A, B, and C, the 22.7% that felt sufficiently trained in security and the 23.3% that perceived the importance of the terminals’ content to hackers, appeared significantly lower next to the 51.31% of the 1200 Finnish professionals reporting bring sufficiently aware of the information and the cybersecurity matters pertaining to their job.…”
Section: Discussionmentioning
confidence: 52%
“…Several endeavors towards assessing healthcare personnel’s cybersecurity culture were based on surveys. Indicatively, the surveys in Poland [ 21 ] and Finland [ 22 ] reported that medical professionals lack sufficient cybersecurity training. The analysis in [ 23 ] confirmed human error as one of the most common reasons for security incidents in hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…For certain types of documents, such as legal, medical, or governmental records, there are often specific regulations governing how they must be scanned, stored, and protected (Hyla and Fabisiak, 2020). Ensuring compliance with these regulations is crucial for maintaining the integrity and security of the documents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, employees should be aware of cyber risks and be familiar with security measures and actions to be taken in case of damage. Various studies, therefore, investigating the influence of human awareness on the success of security programs (Zwilling et al, 2020) examine the level of knowledge of the test persons and the quality of safety training (Hyla and Fabisiak, 2020) and aim to highlight and combine methods that strengthen the security awareness of employees. In this context, the research shows positive effects especially in the combination of different measures (Abawajy, 2014).…”
Section: Organizational Aspects Of Cybersecuritymentioning
confidence: 99%